Presentación Revista Última Década N° 62 - Duarte Quapper, Klaudio (Última Década, 2024)
Welcome to the issue N°62 of our journal. The variety of subjects that have been covered is present through excellent contributions, opening a wide range of perspectives from the youth realities of Chile and Latin America. This issue has been organized from seven different articles arranged in two sections, an interview, and a review.